Indonesian Pre-Service English Teacher Identity Construction in Team-Teaching Context - Arkana Hady; Ahmad Amin Dalimunthe; Rahmah Fithriani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Forming a teacher's identity is crucial for becoming an educator who can appropriately position themselves within the social environment, particularly in the classroom. Pre-service teachers, such as students majoring in teacher education, need opportunities to develop their identity beyond what is formed through their academic experiences at university. To foster this development, team-teaching in schools is essential. However, there is still limited studies that have explored how team-teaching, where pre-service English teachers and mentor teachers collaborate in a classroom, can influence the construction of teacher identity. This study aims to examine how team-teaching helps reconstruct pre-service English teachers’ identity in the context of an EFL (English as a Foreign Language) classroom. Using a phenomenological qualitative approach, the study explores the experiences of three pre-service English teachers during team-teaching. The results show that although students initially faced challenges such as nervousness, anxiety, and limited understanding with mentor teachers, they gradually adapted and actively engaged in team teaching. This experience shaped their identity as English teachers as pedagogical facilitators, while also fostering autonomous and self-regulated teachers prepared for independent teaching.